Layered hydrogel bead-coated biological membrane and preparation method thereof
By designing a layered hydrogel-encapsulated biofilm, using an inner core layer formed by cross-linking sodium alginate and calcium chloride and an outer layer of chitosan-cellulose membrane, the structural instability and bacterial dispersion problems of the in vitro biofilm model were solved, achieving a biofilm simulation with high stability and biocompatibility.
Patent Information
- Application Number
- CN202510876021.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-19
AI Technical Summary
Existing in vitro biofilm models have problems such as structural instability, uncontrolled bacterial dispersion and poor biocompatibility, making it difficult to accurately simulate the dynamic balance and complex behavior of biofilms.
A layered hydrogel-coated bead biofilm is used. The inner layer is a porous hydrogel bead core formed by cross-linking sodium alginate and calcium chloride, and the outer layer is coated with a chitosan-cellulose hydrogel membrane. A stable three-dimensional structure is formed through ionic and hydrogen bond cross-linking to simulate the natural microenvironment of the biofilm.
It improves the long-term stability and bacterial retention rate of the biofilm model, simulates the natural microenvironment of the biofilm, enhances the permeability of nutrients and bacterial activity, and is suitable for the study of common clinical strains.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of biofilm materials, and in particular to a layered hydrogel-encapsulated bead biofilm and a preparation method thereof. Background Art
[0002] Biofilms are complex three-dimensional aggregates composed of microorganisms and their secreted extracellular polymer matrices, and are widely present in the natural environment and within organisms. Their core characteristics include strong antibiotic resistance, vertical gene transfer capabilities, and dynamic microenvironmental regulation mechanisms, and are key factors contributing to chronic infections, biocorrosion of industrial equipment, and difficulties in degrading environmental pollutants. Therefore, studying the formation mechanisms, drug resistance characteristics, and intervention strategies of biofilms is of great significance for medical treatment, industrial defense, and environmental protection. As a research vehicle, in vitro biofilm models provide a controllable and efficient experimental platform for revealing the behavioral patterns of biofilms and evaluating the efficacy of antimicrobial agents by simulating the in vivo microenvironment.
[0003] Currently, methods for preparing in vitro biofilm models are primarily categorized into two types: two-dimensional (2D) and three-dimensional (3D). 2D models typically utilize plate culture methods, either static or with low-speed oscillation, to form attached biofilms. These methods are simple to operate and low-cost, making them widely used for studying fundamental mechanisms such as biofilm adhesion and initial growth. 3D models, on the other hand, utilize scaffold materials to construct a three-dimensional space, mimicking the natural structure of biofilms.
[0004] In view of the above-mentioned prior art, the inventors found that the existing preparation methods still have significant defects. Due to the lack of three-dimensional spatial structure, the 2D model cannot simulate the nutrient gradient, metabolic heterogeneity and EPS network inside the biofilm, resulting in significant differences between its research results on complex behaviors such as drug resistance and chronic infection and the actual in vivo. Although the 3D model is better in spatial simulation, it faces the following challenges: (1) Insufficient matrix stability. For example, alginate hydrogels rely on ionic cross-linking and are easily disintegrated within 2-3 days due to calcium loss or enzymatic hydrolysis, making it difficult to maintain long-term culture; (2) Uncontrolled bacterial dispersion. Bacteria on the surface of hydrogels or beads easily detach from the matrix and enter the culture medium, resulting in the model being unable to accurately reflect the dynamic balance of "fixation-dispersion" of the biofilm; (3) Limited material biocompatibility. Some synthetic polymers may inhibit bacterial activity or interfere with EPS secretion, affecting the biological authenticity of the model. In addition, although the microfluidic model can simulate a dynamic environment, its equipment is complex and the operating cost is high, making it difficult to popularize and apply. Therefore, the development of an in vitro biofilm model with stable structure, strong bacterial retention and good biocompatibility is still a technical problem that needs to be solved in this field. Summary of the Invention
[0005] Based on the technical problems existing in the above-mentioned prior art, the present invention provides a layered hydrogel-encapsulated bead biofilm and a preparation method thereof.
[0006] In a first aspect, the present application provides a layered hydrogel-encapsulated bead biofilm, which adopts the following technical solutions: A layered hydrogel bead biofilm comprises a hydrogel bead inner core layer and a hydrogel coating layer sequentially coated from the inside out. The hydrogel bead inner core layer is formed by cross-linking sodium alginate and calcium chloride, and the mixing ratio of the sodium alginate to the calcium chloride is (1-2): (4-6).
[0007] Through the above technical solution, the present application optimizes the core structure of the layered hydrogel bead biofilm, through the hydrogel bead inner core layer and the hydrogel coating layer coated in sequence from the inside to the outside. Among them, the raw materials of the hydrogel bead inner core layer are sodium alginate and calcium chloride, which are mixed and formed by ionic crosslinking. Sodium alginate, as a natural polysaccharide, has good biocompatibility and gelling properties. After cross-linking reaction with the calcium ions of calcium chloride, it can form hydrogel beads with a porous network structure, providing a three-dimensional load space for bacteria; the concentration and ratio of calcium chloride directly affect the cross-linking density: if the sodium alginate ratio is too high, the gel porosity is reduced, which may limit the diffusion of bacterial metabolites; if the calcium chloride ratio is too high, the cross-linking is insufficient, and the gel strength is insufficient and easy to disintegrate. By limiting the ratio, the mechanical strength of the inner core layer is guaranteed, the structural integrity can be maintained, and the porosity is optimized, which is conducive to the penetration of nutrients and the maintenance of bacterial activity, laying a stable foundation for the construction of the subsequent coating layer.
[0008] Furthermore, the hydrogel coating layer is a chitosan-cellulose hydrogel membrane coating layer.
[0009] Through the above technical solution, the present application further defines the specific material of the hydrogel coating layer as a chitosan-cellulose hydrogel membrane. Chitosan is a deacetylated chitin with a positive charge and good film-forming properties; cellulose is a natural high molecular weight polysaccharide with strong hydrophilicity and stable structure. The two interact through hydrogen bonds in an acidic environment to form a composite hydrogel membrane as the outer coating structure. The addition of chitosan can enhance the antibacterial properties of the membrane, while forming a hydrogen bond network with the hydroxyl groups of cellulose to improve the mechanical toughness of the membrane; cellulose regulates the hydration capacity of the membrane through hydrophilic groups to avoid excessive drying or swelling of the membrane. This composite membrane forms a synergistic structure with the calcium alginate beads in the inner core layer that is "soft inside and tough outside": the inner core layer provides a bacterial load space, and the outer membrane inhibits the dispersion of bacteria into the culture medium through a physical barrier, while retaining the permeation channel for nutrients, significantly improving the long-term stability of the model.
[0010] Furthermore, the inner core layer of the hydrogel beads is loaded with a bacterial suspension.
[0011] Through the above technical solution, the present application further defines the inner core layer of the gel beads as a functional layer "loaded with bacterial suspension". The calcium alginate hydrogel beads in the inner core layer serve as a carrier, and its porous structure can evenly wrap the bacterial suspension to simulate the natural microenvironment of the biofilm. The hydration characteristics of calcium alginate are similar to those of human tissue, which can provide bacteria with a moist environment close to that in the body, avoiding bacterial inactivation due to matrix drying; at the same time, the pore size of the gel matches the pore size of the biofilm EPS, allowing the free diffusion of nutrients and metabolic waste, and maintaining the normal metabolic activities of bacteria. By loading the bacterial suspension, the inner core layer not only achieves the three-dimensional fixation of bacteria, but also provides a spatial basis for the subsequent formation of the biofilm, making the model closer to the growth pattern of natural biofilms.
[0012] Furthermore, the bacterial suspension includes at least one of an Escherichia coli suspension, a Pseudomonas aeruginosa suspension, or a Staphylococcus aureus suspension.
[0013] Through the above technical solution, this application further limits the specific types of bacterial suspension to include at least one of Escherichia coli, Pseudomonas aeruginosa, or Staphylococcus aureus. These three strains are common biofilm-forming bacteria in clinical practice: E. coli is prone to causing urinary tract infection biofilms, Pseudomonas aeruginosa is a major pathogen of lung infections in cystic fibrosis patients, and Staphylococcus aureus is closely associated with implant-related infections. Selecting these strains as payloads directly connects the model to real-world clinical scenarios, enhancing the targeted nature of the research.
[0014] Furthermore, the bacterial suspension is prepared using the following technical solution: The target strain was inoculated on an agar plate, and a single colony was picked and inoculated into a liquid culture medium. After shaking culture, the bacterial solution was diluted to prepare a bacterial suspension.
[0015] Through the above technical solution, this application obtains an active and stable bacterial suspension through a three-step standardized process of "inoculation-culture-dilution". First, the target strain is inoculated on an agar plate, and a single colony is separated by solid culture medium; after picking a single colony and inoculating it into a liquid culture medium, shaking and culturing at 37°C can promote the logarithmic growth of bacteria; finally, the bacterial solution is diluted to an appropriate concentration to ensure that the bacteria are evenly distributed when subsequently mixed with sodium alginate. This preparation method ensures the uniformity of activity and concentration of the bacterial suspension by controlling the culture conditions and dilution ratio, providing quality-controlled raw materials for the subsequent bacterial loading of the inner core layer of the hydrogel beads, and is a key prerequisite for the repeatable preparation of the model.
[0016] In a second aspect, the present application discloses a method for preparing a layered hydrogel-encapsulated bead biofilm, using the following technical solutions: A method for preparing a layered hydrogel-encapsulated bead biofilm comprises the following steps: The bacterial suspension was centrifuged, the supernatant was discarded, and the mixture was mixed with a 5% sodium alginate solution until the final sodium alginate concentration was 3%. The mixture was collected and then dropwise added with a 10% calcium chloride solution. The mixture was stirred to form hydrogel beads, and the inner core layer of the hydrogel beads was collected by centrifugation. The inner core layer of the hydrogel beads was mixed with a 5% by mass cellulose solution, and 1 mL was applied to a glass slide. The solution was covered with a 3% by mass chitosan solution, and the coverslip was lightly pressed to promote hydrogen bond cross-linking between chitosan and cellulose to prepare a stratified hydrogel-encapsulated biofilm.
[0017] Through the above technical solution, this application defines a method for preparing a layered hydrogel-encapsulated biofilm. In the specific operation, centrifuging the bacterial suspension can remove impurities from the culture medium, and mixing it with sodium alginate to a final concentration of 3% can balance the gel strength and bacterial load; the mixture is dropped into a calcium chloride solution and stirred to form hydrogel beads of uniform size through ionic cross-linking; after coating the cellulose-bead mixture, it is covered with a chitosan solution and cross-linked by hydrogen bonds to form a 0.5-1mm thick coating film, which avoids nutrient penetration barriers caused by excessively thick membranes and prevents bacterial leakage caused by excessively thin membranes. This method achieves a layered structure of "core-loaded bacteria-outer-layer physical isolation" through multi-step precise control, which improves the bacterial retention rate of the model compared to simple calcium alginate beads.
[0018] Furthermore, the volume ratio of the chitosan solution to the inner core layer of the hydrogel beads is 1:1.
[0019] Through the above technical solution, the present application limits the volume ratio of the chitosan solution to the inner core layer of the hydrogel beads to 1:1. As the main raw material of the coating layer, the ratio of the volume of the chitosan solution to the inner core layer directly affects the coating effect: if the volume of the chitosan is too large, the coating film is too thick, which may hinder the penetration of nutrients into the inner core layer; if the volume is too small, the film layer is too thin and cannot effectively inhibit the dispersion of bacteria. The ratio balances the film-forming properties of chitosan and the hydrophilicity of cellulose to make the thickness of the coating film uniform, which not only retains the mechanical strength of the membrane, but also maintains the water permeability of the membrane. This optimized ratio ensures the close combination of the coating layer and the inner core layer, avoids structural damage due to stratification, and is a key parameter to ensure the long-term stability of the model.
[0020] In summary, this application has the following beneficial effects: First, the present application optimizes the core structure of the layered hydrogel bead biofilm, through the hydrogel bead inner core layer and the hydrogel coating layer coated in sequence from the inside to the outside. Among them, the raw materials of the hydrogel bead inner core layer are sodium alginate and calcium chloride, which are mixed and formed by ionic cross-linking. Sodium alginate, as a natural polysaccharide, has good biocompatibility and gelling properties. After cross-linking reaction with the calcium ions of calcium chloride, it can form hydrogel beads with a porous network structure, providing a three-dimensional load space for bacteria; the concentration and ratio of calcium chloride directly affect the cross-linking density: if the sodium alginate ratio is too high, the gel porosity is reduced, which may limit the diffusion of bacterial metabolites; if the calcium chloride ratio is too high, the cross-linking is insufficient, and the gel strength is insufficient and easy to disintegrate. By limiting the ratio, the mechanical strength of the inner core layer is guaranteed, the structural integrity can be maintained, and the porosity is optimized, which is conducive to the penetration of nutrients and the maintenance of bacterial activity, laying a stable foundation for the construction of the subsequent coating layer.
[0021] Second, this application further defines the inner core layer of the gel beads as a functional layer "loaded with bacterial suspension." The calcium alginate hydrogel beads in the inner core layer serve as a carrier, and their porous structure can evenly wrap the bacterial suspension to simulate the natural microenvironment of the biofilm. The hydration characteristics of calcium alginate are similar to those of human tissue, which can provide bacteria with a moist environment close to that in the body, avoiding bacterial inactivation due to matrix drying; at the same time, the pore size of the gel matches the pore size of the biofilm EPS, allowing the free diffusion of nutrients and metabolic waste, and maintaining the normal metabolic activities of bacteria. By loading the bacterial suspension, the inner core layer not only achieves three-dimensional fixation of bacteria, but also provides a spatial basis for the subsequent formation of the biofilm, making the model closer to the growth pattern of natural biofilms.
[0022] Third, this application defines a method for preparing a layered hydrogel-encapsulated biofilm. In the specific operation, centrifuging the bacterial suspension can remove impurities from the culture medium, and mixing it with sodium alginate to a final concentration of 3% can balance the gel strength and bacterial load; the mixture is dropped into a calcium chloride solution and stirred to form hydrogel beads of uniform size through ionic cross-linking; after coating the cellulose-bead mixture, it is covered with a chitosan solution, and a 0.5-1mm thick coating is formed through hydrogen bond cross-linking, which not only avoids nutrient penetration barriers caused by excessively thick membranes, but also prevents bacterial leakage caused by excessively thin membranes. This method achieves a layered structure of "core-loaded bacteria-outer-layer physical isolation" through multi-step precise control, which improves the bacterial retention rate of the model compared to simple calcium alginate beads. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments.
[0024] Example 1 Escherichia coli ATCC 25922 was selected as the target strain. The specific steps are as follows: (1) Activation culture: Streak the frozen E. coli culture onto LB agar plates (10 g / L tryptone, 5 g / L yeast extract, 10 g / L NaCl, 15 g / L agar), incubate at 37°C for 16 h, pick a single colony and inoculate into 5 mL LB liquid medium (without agar), incubate at 37°C and 200 rpm with shaking overnight (12 h) to obtain the logarithmic phase culture.
[0025] (2) Dilution treatment: Take the overnight culture and dilute it with LB liquid medium to OD 600 = 0.1 (to obtain a bacterial suspension. Transfer the bacterial suspension to a 15 mL centrifuge tube and centrifuge at 5000 g for 10 min at 4°C. Discard the supernatant and resuspend the pellet in 2 mL of fresh LB to obtain wet cells.
[0026] (3) Mixing and cross-linking: The wet bacteria were mixed with 5% (w / v) sodium alginate solution (5 g of sodium alginate was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1, and stirred evenly until the final concentration of sodium alginate was 3% (w / v) to obtain a bacteria-sodium alginate mixture.
[0027] (4) Drop-casting: The mixed solution was loaded into a 1 mL syringe. Under the action of a magnetic stirrer (rotation speed 300 rpm), the mixed solution was dripped drop by drop into 100 mL of 10% (w / v) calcium chloride solution (10 g of CaCl2·2H2O was weighed and dissolved in 100 mL of ultrapure water). The dripping rate was controlled at 1 drop / s. After the dripping was completed, stirring was continued for 30 min to form hydrogel beads with a diameter of about 1.5 mm.
[0028] (5) Collecting the inner core layer: Transfer the hydrogel beads to a 50 mL centrifuge tube, centrifuge at 4°C and 3000 g for 5 min, discard the supernatant, and wash twice with PBS buffer (pH 7.4) to obtain the inner core layer of the bacteria-loaded hydrogel beads.
[0029] (6) Preparation of cellulose mixture: The inner core layer of the hydrogel beads was mixed with 5% (w / v) cellulose solution (5 g of sodium carboxymethyl cellulose was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1. After thorough shaking, 1 mL was evenly coated on a glass slide (25 mm × 75 mm × 1 mm).
[0030] (7) Chitosan cross-linking: Take 1 mL of 3% (w / v) chitosan solution (weigh 3 g of chitosan and dissolve it in 100 mL of 1% HCl solution, adjust the pH to 5.5), evenly cover the surface of the cellulose-bead mixture, and gently press a coverslip (24 mm × 50 mm × 0.15 mm) to allow chitosan and cellulose to fully contact. Let it stand at room temperature for 30 min. After the hydrogen bond cross-linking is completed, carefully remove the coverslip to obtain a layered hydrogel-encapsulated bead biofilm.
[0031] Example 2 Escherichia coli ATCC 25922 was selected as the target strain. The specific steps are as follows: (1) Activation culture: Streak the frozen E. coli culture onto LB agar plates (10 g / L tryptone, 5 g / L yeast extract, 10 g / L NaCl, 15 g / L agar), incubate at 37°C for 16 h, pick a single colony and inoculate into 5 mL LB liquid medium (without agar), incubate at 37°C and 200 rpm with shaking overnight (12 h) to obtain the logarithmic phase culture.
[0032] (2) Dilution treatment: Take the overnight culture and dilute it with LB liquid medium to OD 600 = 0.1 (to obtain a bacterial suspension. Transfer the bacterial suspension to a 15 mL centrifuge tube and centrifuge at 5000 g for 10 min at 4°C. Discard the supernatant and resuspend the pellet in 2 mL of fresh LB to obtain wet cells.
[0033] (3) Mixing and cross-linking: The wet bacteria were mixed with 5% (w / v) sodium alginate solution (5 g of sodium alginate was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1, and stirred evenly until the final concentration of sodium alginate was 3% (w / v) to obtain a bacteria-sodium alginate mixture.
[0034] (4) Drop-casting: The mixed solution was loaded into a 1 mL syringe. Under the action of a magnetic stirrer (rotation speed 300 rpm), the mixed solution was dripped dropwise into 40 mL of 10% (w / v) calcium chloride solution (10 g of CaCl2·2H2O was weighed and dissolved in 100 mL of ultrapure water). The dripping rate was controlled at 1 drop / s. After the dripping was completed, stirring was continued for 30 min to form hydrogel beads with a diameter of about 1.3 mm.
[0035] (5) Collecting the inner core layer: Transfer the hydrogel beads to a 50 mL centrifuge tube, centrifuge at 4°C and 3000 g for 5 min, discard the supernatant, and wash twice with PBS buffer (pH 7.4) to obtain the inner core layer of the bacteria-loaded hydrogel beads.
[0036] (6) Preparation of cellulose mixture: The inner core layer of the hydrogel beads was mixed with 5% (w / v) cellulose solution (5 g of sodium carboxymethyl cellulose was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1. After thorough shaking, 1 mL was evenly coated on a glass slide (25 mm × 75 mm × 1 mm).
[0037] (7) Chitosan cross-linking: Take 1 mL of 3% (w / v) chitosan solution (weigh 3 g of chitosan and dissolve it in 100 mL of 1% HCl solution, adjust the pH to 5.5), evenly cover the surface of the cellulose-bead mixture, and gently press a coverslip (24 mm × 50 mm × 0.15 mm) to allow chitosan and cellulose to fully contact. Let it stand at room temperature for 30 min. After the hydrogen bond cross-linking is completed, carefully remove the coverslip to obtain a layered hydrogel-encapsulated bead biofilm.
[0038] Example 3 Escherichia coli ATCC 25922 was selected as the target strain. The specific steps are as follows: (1) Activation culture: Streak the frozen E. coli culture onto LB agar plates (10 g / L tryptone, 5 g / L yeast extract, 10 g / L NaCl, 15 g / L agar), incubate at 37°C for 16 h, pick a single colony and inoculate into 5 mL LB liquid medium (without agar), incubate at 37°C and 200 rpm with shaking overnight (12 h) to obtain the logarithmic phase culture.
[0039] (2) Dilution treatment: Take the overnight culture and dilute it with LB liquid medium to OD 600 = 0.1 (to obtain a bacterial suspension. Transfer the bacterial suspension to a 15 mL centrifuge tube and centrifuge at 5000 g for 10 min at 4°C. Discard the supernatant and resuspend the pellet in 2 mL of fresh LB to obtain wet cells.
[0040] (3) Mixing and cross-linking: The wet bacteria were mixed with 5% (w / v) sodium alginate solution (5 g of sodium alginate was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1, and stirred evenly until the final concentration of sodium alginate was 3% (w / v) to obtain a bacteria-sodium alginate mixture.
[0041] (4) Drop-casting: The mixed solution was loaded into a 1 mL syringe. Under the action of a magnetic stirrer (rotation speed 300 rpm), the mixed solution was dripped dropwise into 50 mL of 10% (w / v) calcium chloride solution (10 g of CaCl2·2H2O was weighed and dissolved in 100 mL of ultrapure water). The dripping rate was controlled at 1 drop / s. After the dripping was completed, stirring was continued for 30 min to form hydrogel beads with a diameter of about 1.5 mm.
[0042] (5) Collecting the inner core layer: Transfer the hydrogel beads to a 50 mL centrifuge tube, centrifuge at 4°C and 3000 g for 5 min, discard the supernatant, and wash twice with PBS buffer (pH 7.4) to obtain the inner core layer of the bacteria-loaded hydrogel beads.
[0043] (6) Preparation of cellulose mixture: The inner core layer of the hydrogel beads was mixed with 5% (w / v) cellulose solution (5 g of sodium carboxymethyl cellulose was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1. After thorough shaking, 1 mL was evenly coated on a glass slide (25 mm × 75 mm × 1 mm).
[0044] (7) Chitosan cross-linking: Take 1 mL of 3% (w / v) chitosan solution (weigh 3 g of chitosan and dissolve it in 100 mL of 1% HCl solution, adjust the pH to 5.5), evenly cover the surface of the cellulose-bead mixture, and gently press a coverslip (24 mm × 50 mm × 0.15 mm) to allow chitosan and cellulose to fully contact. Let it stand at room temperature for 30 min. After the hydrogen bond cross-linking is completed, carefully remove the coverslip to obtain a layered hydrogel-encapsulated bead biofilm.
[0045] Example 4 Escherichia coli ATCC 25922 was selected as the target strain. The specific steps are as follows: (1) Activation culture: Streak the frozen E. coli culture onto LB agar plates (10 g / L tryptone, 5 g / L yeast extract, 10 g / L NaCl, 15 g / L agar), incubate at 37°C for 16 h, pick a single colony and inoculate into 5 mL LB liquid medium (without agar), incubate at 37°C and 200 rpm with shaking overnight (12 h) to obtain the logarithmic phase culture.
[0046] (2) Dilution treatment: Take the overnight culture and dilute it with LB liquid medium to OD 600 = 0.1 (to obtain a bacterial suspension. Transfer the bacterial suspension to a 15 mL centrifuge tube and centrifuge at 5000 g for 10 min at 4°C. Discard the supernatant and resuspend the pellet in 2 mL of fresh LB to obtain wet cells.
[0047] (3) Mixing and cross-linking: The wet bacteria were mixed with 5% (w / v) sodium alginate solution (5 g of sodium alginate was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1, and stirred evenly until the final concentration of sodium alginate was 3% (w / v) to obtain a bacteria-sodium alginate mixture.
[0048] (4) Drop-casting: The mixed solution was loaded into a 1 mL syringe. Under the action of a magnetic stirrer (rotation speed 300 rpm), the mixed solution was dripped dropwise into 60 mL of 10% (w / v) calcium chloride solution (10 g of CaCl2·2H2O was weighed and dissolved in 100 mL of ultrapure water). The dripping rate was controlled at 1 drop / s. After the dripping was completed, stirring was continued for 30 min to form hydrogel beads with a diameter of about 1.5 mm.
[0049] (5) Collecting the inner core layer: Transfer the hydrogel beads to a 50 mL centrifuge tube, centrifuge at 4°C and 3000 g for 5 min, discard the supernatant, and wash twice with PBS buffer (pH 7.4) to obtain the inner core layer of the bacteria-loaded hydrogel beads.
[0050] (6) Preparation of cellulose mixture: The inner core layer of the hydrogel beads was mixed with 5% (w / v) cellulose solution (5 g of sodium carboxymethyl cellulose was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1. After thorough shaking, 1 mL was evenly coated on a glass slide (25 mm × 75 mm × 1 mm).
[0051] (7) Chitosan cross-linking: Take 1 mL of 3% (w / v) chitosan solution (weigh 3 g of chitosan and dissolve it in 100 mL of 1% HCl solution, adjust the pH to 5.5), evenly cover the surface of the cellulose-bead mixture, and gently press a coverslip (24 mm × 50 mm × 0.15 mm) to allow chitosan and cellulose to fully contact. Let it stand at room temperature for 30 min. After the hydrogen bond cross-linking is completed, carefully remove the coverslip to obtain a layered hydrogel-encapsulated bead biofilm.
[0052] Example 5 Pseudomonas aeruginosa ATCC 27853 was selected as the target strain. The specific steps are as follows: (1) Activation culture: Streak the frozen E. coli culture onto LB agar plates (10 g / L tryptone, 5 g / L yeast extract, 10 g / L NaCl, 15 g / L agar), incubate at 37°C for 16 h, pick a single colony and inoculate into 5 mL LB liquid medium (without agar), incubate at 37°C and 200 rpm with shaking overnight (12 h) to obtain the logarithmic phase culture.
[0053] (2) Dilution treatment: Take the overnight culture and dilute it with LB liquid medium to OD 600 = 0.1 (to obtain a bacterial suspension. Transfer the bacterial suspension to a 15 mL centrifuge tube and centrifuge at 5000 g for 10 min at 4°C. Discard the supernatant and resuspend the pellet in 2 mL of fresh LB to obtain wet cells.
[0054] (3) Mixing and cross-linking: The wet bacteria were mixed with 5% (w / v) sodium alginate solution (5 g of sodium alginate was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1, and stirred evenly until the final concentration of sodium alginate was 3% (w / v) to obtain a bacteria-sodium alginate mixture.
[0055] (4) Drop-casting: The mixed solution was loaded into a 1 mL syringe. Under the action of a magnetic stirrer (rotation speed 300 rpm), the mixed solution was dripped drop by drop into 100 mL of 10% (w / v) calcium chloride solution (10 g of CaCl2·2H2O was weighed and dissolved in 100 mL of ultrapure water). The dripping rate was controlled at 1 drop / s. After the dripping was completed, stirring was continued for 30 min to form hydrogel beads with a diameter of about 1.5 mm.
[0056] (5) Collecting the inner core layer: Transfer the hydrogel beads to a 50 mL centrifuge tube, centrifuge at 4°C and 3000 g for 5 min, discard the supernatant, and wash twice with PBS buffer (pH 7.4) to obtain the inner core layer of the bacteria-loaded hydrogel beads.
[0057] (6) Preparation of cellulose mixture: The inner core layer of the hydrogel beads was mixed with 5% (w / v) cellulose solution (5 g of sodium carboxymethyl cellulose was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1. After thorough shaking, 1 mL was evenly coated on a glass slide (25 mm × 75 mm × 1 mm).
[0058] (7) Chitosan cross-linking: Take 1 mL of 3% (w / v) chitosan solution (weigh 3 g of chitosan and dissolve it in 100 mL of 1% HCl solution, adjust the pH to 5.5), evenly cover the surface of the cellulose-bead mixture, and gently press a coverslip (24 mm × 50 mm × 0.15 mm) to allow chitosan and cellulose to fully contact. Let it stand at room temperature for 30 min. After the hydrogen bond cross-linking is completed, carefully remove the coverslip to obtain a layered hydrogel-encapsulated bead biofilm.
[0059] Example 6 Staphylococcus aureus ATCC 29213 was selected as the target strain. The specific steps are as follows: (1) Activation culture: Streak the frozen E. coli culture onto LB agar plates (10 g / L tryptone, 5 g / L yeast extract, 10 g / L NaCl, 15 g / L agar), incubate at 37°C for 16 h, pick a single colony and inoculate into 5 mL LB liquid medium (without agar), incubate at 37°C and 200 rpm with shaking overnight (12 h) to obtain the logarithmic phase culture.
[0060] (2) Dilution treatment: Take the overnight culture and dilute it with LB liquid medium to OD 600 = 0.1 (to obtain a bacterial suspension. Transfer the bacterial suspension to a 15 mL centrifuge tube and centrifuge at 5000 g for 10 min at 4°C. Discard the supernatant and resuspend the pellet in 2 mL of fresh LB to obtain wet cells.
[0061] (3) Mixing and cross-linking: The wet bacteria were mixed with 5% (w / v) sodium alginate solution (5 g of sodium alginate was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1, and stirred evenly until the final concentration of sodium alginate was 3% (w / v) to obtain a bacteria-sodium alginate mixture.
[0062] (4) Drop-casting: The mixed solution was loaded into a 1 mL syringe. Under the action of a magnetic stirrer (rotation speed 300 rpm), the mixed solution was dripped drop by drop into 100 mL of 10% (w / v) calcium chloride solution (10 g of CaCl2·2H2O was weighed and dissolved in 100 mL of ultrapure water). The dripping rate was controlled at 1 drop / s. After the dripping was completed, stirring was continued for 30 min to form hydrogel beads with a diameter of about 1.5 mm.
[0063] (5) Collecting the inner core layer: Transfer the hydrogel beads to a 50 mL centrifuge tube, centrifuge at 4°C and 3000 g for 5 min, discard the supernatant, and wash twice with PBS buffer (pH 7.4) to obtain the inner core layer of the bacteria-loaded hydrogel beads.
[0064] (6) Preparation of cellulose mixture: The inner core layer of the hydrogel beads was mixed with 5% (w / v) cellulose solution (5 g of sodium carboxymethyl cellulose was dissolved in 100 mL of ultrapure water and sterilized by high pressure) at a volume ratio of 1:1. After thorough shaking, 1 mL was evenly coated on a glass slide (25 mm × 75 mm × 1 mm).
[0065] (7) Chitosan cross-linking: Take 1 mL of 3% (w / v) chitosan solution (weigh 3 g of chitosan and dissolve it in 100 mL of 1% HCl solution, adjust the pH to 5.5), evenly cover the surface of the cellulose-bead mixture, and gently press a coverslip (24 mm × 50 mm × 0.15 mm) to allow chitosan and cellulose to fully contact. Let it stand at room temperature for 30 min. After the hydrogen bond cross-linking is completed, carefully remove the coverslip to obtain a layered hydrogel-encapsulated bead biofilm.
[0066] Performance testing Compression strength: The force (N) required to compress the beads by 50% was measured using a texture analyzer (TA.XT Plus); Bacterial retention: After 9 days of culture, take the culture medium to measure OD 600 value (the higher the OD value, the more severe the bacterial dispersion); Model disintegration rate: After 9 days of culture, the proportion of ruptured / swollen hydrogel beads was calculated (disintegration rate = number of disintegrated beads / total number of beads × 100%).
[0067] The layered hydrogel-encapsulated bead biofilms prepared in Examples 1-5 were subjected to mechanical property tests, and the results are shown in Table 1 below: Table 1 Performance test table
[0068] From the above examples 1-6 and the comparison of the test results in Table 1, it can be found that: The present application optimizes the core structure of the layered hydrogel bead biofilm, through the hydrogel bead inner core layer and the hydrogel coating layer coated in sequence from the inside to the outside. Among them, the raw materials of the hydrogel bead inner core layer are sodium alginate and calcium chloride, the two are mixed and formed by ionic cross-linking. Combined with Table 1, it can be seen that the present application directly affects the cross-linking density through the concentration and proportion of calcium chloride: if the sodium alginate ratio is too high, the gel porosity is reduced, which may limit the diffusion of bacterial metabolites; if the calcium chloride ratio is too high, the cross-linking is insufficient, the gel strength is insufficient and it is easy to disintegrate. By limiting the ratio, the mechanical strength of the inner core layer is guaranteed and the structural integrity can be maintained, and the porosity is optimized, which is conducive to the penetration of nutrients and the maintenance of bacterial activity, laying a stable foundation for the construction of the subsequent coating layer.
[0069] The present invention has been described in detail above with reference to specific embodiments and exemplary examples. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will appreciate that various equivalent substitutions, modifications, or improvements may be made to the technical solutions and implementations of the present invention without departing from the spirit and scope of the present invention, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be determined by the appended claims.
[0070] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of conflict, the definitions in this specification shall prevail.
[0071] When this specification uses the prefix "well known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, the objects introduced by the prefix include those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become generally recognized in the art to be suitable for similar purposes.
[0072] In the context of this specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
Claims
1. A layered hydrogel-encapsulated biofilm, characterized in that: The hydrogel bead inner core layer and the hydrogel coating layer are sequentially coated from the inside to the outside. The hydrogel bead inner core layer is formed by cross-linking sodium alginate and calcium chloride. The mixing ratio of the sodium alginate and the calcium chloride is (1-2): (4-6).
2. The layered hydrogel-encapsulated bead biofilm according to claim 1, characterized in that: The hydrogel coating layer is a chitosan-cellulose hydrogel film coating layer.
3. The layered hydrogel-encapsulated bead biofilm according to claim 1, characterized in that: The inner core layer of the hydrogel beads is loaded with a bacterial suspension.
4. The layered hydrogel-encapsulated bead biofilm according to claim 3, characterized in that: The bacterial suspension includes at least one of an Escherichia coli suspension, a Pseudomonas aeruginosa suspension or a Staphylococcus aureus suspension.
5. The layered hydrogel-encapsulated bead biofilm according to claim 4, characterized in that: The bacterial suspension is prepared by the following technical solution: The target strain was inoculated on an agar plate, and a single colony was picked and inoculated into a liquid culture medium. After shaking culture, the bacterial solution was diluted to prepare a bacterial suspension.
6. The method for preparing a layered hydrogel-encapsulated bead biofilm according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: The bacterial suspension was centrifuged, the supernatant was discarded, and the mixture was mixed with a 5% sodium alginate solution until the final sodium alginate concentration was 3%. The mixture was collected and then dropwise added with a 10% calcium chloride solution. The mixture was stirred to form hydrogel beads, and the inner core layer of the hydrogel beads was collected by centrifugation. The inner core layer of the hydrogel beads was mixed with a 5% by mass cellulose solution, and 1 mL was applied to a glass slide. The solution was covered with a 3% by mass chitosan solution, and the coverslip was lightly pressed to promote hydrogen bond cross-linking between chitosan and cellulose to prepare a stratified hydrogel-encapsulated biofilm.
7. The method for preparing a layered hydrogel-encapsulated bead biofilm according to claim 6, characterized in that: The volume ratio of the chitosan solution to the inner core layer of the hydrogel beads is 1:1.